High-resolution spacialization of an Oxisol’s acidity attributes by on-the-go sensing - Corassa, Geomar Mateus; Amado, Telmo Jorge Carneiro; Tabaldi, Fabiano Maurício; Schwalbert, Raí Augusto; Reimche, Geovane Boschmann; Nora, Douglas Dalla; Alba, Paulo José; Horbe, Tiago Andrade Neves (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the relationships between the apparent electric conductivity (ECa), measured by on-the-go sensing, with soil attributes and plant production, besides indirectly mapping with high resolution, the main acidity attributes of an Oxisol in South Brazil. Soil sensing was performed in two crop fields using the Veris 3100 sensor. Soil was sampled at the 0.00–0.15-m soil depth using a hand auger. The corn vigor index (VI) was measured with an optical sensor, and yield was determined using grain yield and moisture sensors. The association of soil acidity attributes with corn yield and ECa was determined with correlation and principal component analyses. ECa was associated with the VI and corn yield. Moreover, in the area with low chemical quality, ECa had a positive relationship with Ca2+ and Mg2+ contents, pH in water, base saturation, sum of bases, and cation exchange capacity; and a negative relationship with Al3+, aluminum saturation, and H+Al3+ values. In the area with better chemical quality, ECa was related to Ca2+ and Mg2+ contents, soil organic matter, and clay content.